The validity of a non-differential global positioning system for assessing player movement patterns in field hockey - MacLeod, H.; Morris, J.; Nevill, A.; Sunderland, C. (Journal of Sports Sciences, 2009)
Nine games players (mean age 23.3 years, s = 2.8; height 1.73 m, s = 0.08; body mass 70.0 kg, s = 12.7) completed 14 laps of a measured circuit that incorporated intermittent running and directional changes, representative of the movements made by field hockey players during match-play. The distances and speeds recorded by a global positioning satellite (GPS) system (Spi Elite™) were compared statistically with speed measurements made using timing gates and distances measured using a calibrated trundle wheel, to establish the criterion validity of the GPS system. A validation of the speed of movement of each participant separately was also made, using data from each timing gate, over a range of speeds. The mean distance recorded by the GPS system was 6821 m (s = 7) and the mean speed was 7.0 km · h-1 (s = 1.9), compared with the actual distance of 6818 m and recorded mean speed of 7.0 km · h-1 (s = 1.9). Pearson correlations (r) among timing gate speed and GPS speed were =0.99 (P < 0.001) and the mean difference and 95% limits of agreement were 0.0 ± 0.9 km · h-1. These results suggest that a GPS system (Spi Elite™) offers a valid tool for measuring speed and distance during match-play, and can quickly provide the scientist, coach, and player with objective information about certain movement patterns during competitive games.